ISSUES OF SHARING SYRDARYA WATER RESOURCES IN CENTRAL ASIA (Scientific journal of the Fergana State University, 2025)
The article is devoted to the analysis of the issues of sharing the water resources of the Syrdarya River in Central Asia. The main focus of the research is on the analysis of the content of the “87th meeting of the Interstate Commission for the Coordination of Water Management”, which was held on November 6, 2024 in Ashgabat, Turkmenistan. In addition, the article analyzes the water balance of the structure for the growing season of 2024, the largest hydraulic structure in Central Asia regulating the flow of the Syrdarya, the Tuktagul reservoir and its significance in the region.